Executive function and contingency management for methamphetamine use disorder in South Africa: a comparison pre- and post-treatment - van Nunen, Lara Jane (Department of Psychiatry and Mental Health, 2021)
Background: Methamphetamine dependence is associated with impairment in executive function, as well as brain functional and structural alterations, findings on the relationship between executive function impairment and brain alterations seem inconsistent. Methamphetamine dependence may respond to contingency management, yet it is unclear if the treatment response is predicted by these neuropsychological, and brain functional and structural changes, and whether treatment alters neuropsychological impairment. I first conducted a systematic review to rigorously assess available findings on the relationship between executive function impairment and brain functional changes. I then explored data from a study of contingency management in methamphetamine dependence with the aims of determining 1) whether treatment response was predicted by executive function impairment and brain functional and structural alterations, and 2) whether treatment led to changes in executive function and brain functional and structural impairment in treatment responders and non-responders. Methods: The systematic review involved a rigorous search and assessment of articles on the association of stimulant use and resting state functional connectivity. In the empirical study, 33 subjects underwent executive function testing, resting state-fMRI, and structural neuroimaging prior to contingency management treatment. Executive function was assessed with the trail making task, the Stroop-word task, and the Connors continuous performance task. Seed-based analysis was used for functional MRI, with a focus on brain regions associated with executive function, and brain structural alterations were assessed using measures of cortical thickness and surface area. In the statistical analysis, first associations of baseline executive function, rs-fMRI, and brain structural alterations with treatment outcome were assessed using linear regression, and second, comparison of executive function, rsfMRI, and brain structural parameters at baseline versus at treatment end in treatment responders and non-responders was undertaken using linear regression, Cohen's d and a change score. Results: The systematic review noted specific associations between executive function impairment and resting state-fMRI. While in the study, treatment responders had improved executive function at baseline as assessed by two measures (faster completion times on the trail making, and greater accuracy on the Connors continuous performance task), but worse executive function on a third measure (lower accuracy on the Stroop word task) when compared with non-responders. No statistically significant differences between groups was found with regards to rsFC, however greater cortical thickness was found in responders brain regions associated with executive function, in comparison to non-responders. Analysis of pre vs post treatment findings showed that in treatment responders there was better executive function after treatment, in comparison to non-responders (as assessed by greater accuracy on the Connors continuous performance task). Furthermore, in treatment responders there was greater increase in cortical volume in regions associated with executive function, than in non-responders. Conclusion: These findings support the hypothesis that better executive function at baseline (task switching and selective attention) is associated with better outcomes in a contingency management trial of 8-weeks. There is also evidence of improved executive function post trial (in selective attention and cortical thickness findings support improved executive function) implying that abstinence as a consequence of a contingency management trial of 8-weeks may improve executive function, a larger sample size would be needed to determine if improvements extend to other regions of executive function